Evaluasi Pelaksanaan Cement Treated Sub-base (CTSB) Pada Proyek Peningkatan Jalan Sukadana - Teluk Batang - Marojahan Rajagukguk; Trifenaus Prabu Hidayat (Universitas Katolik Indonesia Atma Jaya, 2024)
The Sukadana - Teluk Batang road section is a strategic provincial road in Kayong Utara Regency that faces pavement stability issues due to soft subgrade conditions. This research aims to analyze the effectiveness of implementing Cement Treated Sub-base (CTSB) technology with composite cement as an alternative solution for improving road pavement quality. The research methodology includes evaluation of existing conditions, CTSB pavement design planning, trial compaction implementation, and field performance testing and monitoring. The results showed that CTSB application with 10 passes achieved a density level of 98.50% and CBR value reaching 151.54%, far exceeding the specified minimum requirements. The unconfined compressive strength (UCS) value at 7 days reached 25.39 kg/cm², meeting the required strength criteria. Post-construction visual observations showed a homogeneous and stable road surface without indication of structural damage. This research proves that CTSB technology with composite cement is effective in improving subgrade bearing capacity and provides a sustainable solution for road infrastructure development in areas with soft soil characteristics.